Docetaxel Distribution Following Intraperitoneal Administration in Mice - Payam Zahedi; Raquel De Souza; Micheline Piquette-Miller; Christine Allen (Frontiers Media S.A., 2011)
Purpose: Intraperitoneal (IP) chemotherapy with high molecular weight lipophilic antineoplastic agents such as the taxanes has shown promise in clinical trial evaluation for treatment of localized peritoneal cancers. We have previously developed an IP injectable hydrogel formulation (PoLigel) for sustained peritoneal delivery of docetaxel (DTX), and observed significant efficacy in murine models of ovarian cancer when compared to Taxotere®, the FDA approved formulation of DTX. In order to understand the relationship between drug distribution and efficacy, the current study compares the tissue distribution and pharmacokinetics of DTX administered IP in the PoLigel or Taxotere® formulations. Methods: The PoLigel was prepared by blending a water-soluble chitosan derivative, egg phosphatidylcholine and lauric aldehyde with DTX (drug to material ratio 1:8 w/w). DTX concentrations in plasma, heart, liver, spleen, stomach, intestine, kidney and peritoneal muscle were measured over a five day period following IP administration of the PoLigel and Taxotere® formulations in CD-1 female mice. Results: Three days after Taxotere® administration, no detectable levels of DTX were seen in plasma, while sustained DTX plasma levels of 0.06 ug/ml ± 0.01 per day were observed with PoLigel. At five days post Taxotere® administration, only intestine, stomach and peritoneal muscle showed detectable DTX concentrations whereas all tissues and plasma showed sustained DTX levels in mice that received PoLigel. DTX concentrations that resulted from PoLigel administration were significantly higher in the peritoneal cavity and 200 fold higher than concentrations found in plasma. Conclusions: Overall, the PoLigel formulation increases tissue and plasma drug retention and provides sustained DTX levels compared to the clinically used Taxotere® formulation. The sustained DTX levels seen in the peritoneal cavity following IP administration of the PoLigel may be responsible for the improvement in efficacy that has been observed in our previous studies.